Digital Sentiments on Gibran’s Politics: Public Participation and Perception in Social Media Discourse - Isnan Nursalim; Nofriadi Kurnia Putra; Hana Hanifah (CV. Abhinaya Indo Group, 2025)
This study aims to read and analyze public sentiment toward the political narrative constructed by Gibran Rakabuming through his monologue video “Giliran Kita” (Our Turn), delivered by Vice President Gibran Rakabuming Raka and uploaded to his personal YouTube channel, which has attracted significant public attention in a short period of time. In this video, Gibran seeks to encourage the younger generation to take on a role and dare to make breakthroughs amid the current global challenges. However, various reactions reflecting the dynamics of public opinion and perceptions toward the political narrative have emerged widely across social media platforms, particularly on X. This study employs a mixed-methods approach, combining quantitative and qualitative methods. Quantitative methods were used to collect and analyze digital data through web scraping of posts containing the keyword “Gibran” during the period from April 19 to 26, 2025. Based on the findings of this study, the political narrative constructed by Gibran shows positive resonance among users of the X platform, particularly in shaping his image as a representative of the younger generation. The dominance of positive and neutral sentiments indicates that Gibran's political strategy appears to be quite successful, at least on the X platform. These findings reveal that public perception in the digital space is never static, is layered, and is not always objective. Social media is no longer merely a tool for conveying messages but has become a space for political discourse competition and the formation of power legitimacy. Public perceptions of figures like Gibran are shaped through a complex process influenced by the content of messages, the evolving nature of issues, the communication strategies employed, and the roles of active actors in disseminating political narratives in the digital world.